Respuesta :
Answer:
[tex] \star \: \tt \: (8x - 3 {x}^{3} + 10 {x}^{2} ) - ( - 3 {x}^{2} + 11 {x}^{3} - 7)[/tex]
[tex] \longrightarrow \tt \: 8x - 3 {x}^{3} + 10 {x}^{2} + 3 {x}^{2} - 11 {x}^{3} + 7[/tex]
[tex] \longrightarrow \tt \: - 3 {x}^{3} - 11 {x}^{3} + 3 {x}^{2} + 10 {x}^{2} + 8x+ 7[/tex]
[tex] \longrightarrow \boxed{\tt \: - 14 {x}^{3} + 13 {x}^{2} + 8x + 7}[/tex]
- Our final answer is -14x^3 + 13x^2 + 8x + 7 .
--------- HappY LearninG <3 ------------
Step-by-step explanation:
Distribute the Negative Sign:
=8x−3x^3+10x^2−1(−3x^2+11x^3−7)
=8x−3x^3+10x^2−1(−3x^2)−1(11x^3)+(−1)(−7)
=8x-3x^3+10x^2+3x^2−11x^3+7
Combine Like Terms:
=8x−3x^3+10x^2+3x^2−11x^3+7
=(−3x^3−11x^3)+(10x^2+3x^2)+(8x)+(7)
=−14x^3+13x^2+8x+7